Report from the Academic Session “Human and Nature: Between Destruction and Creation” Organized as Part of the 23rd International Congress of Historical Sciences in Poznań on 24th August 2022 - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2022)
Broadly defined environmental history was the context for the session entitled “Human and nature: Between destruction and creation”, organized and conducted on 24th august 2022 by prof. tadeusz Janicki (Faculty of History, UAM, Poznań, Poland) and prof. Dariusz Gwiazdowicz (Department of Forest Protection, Poznań University of Life Sciences, Poland) as part of the 23rd International Congress of Historical Sciences Poznań 2022.